DEFINITION OF BUDGETING AS A COMPONENT OF A DESCRIPTIVE ASSESSMENT OF THE FINANCIAL SOLVENCY OF RUSSIAN ENTERPRISES - S. Yunusova; A. Bodiako (Вестник университета)
Problems of the implementation of the fractal, within branched budgeting system in Russian enterprises. Of necessity unification and harmonization of intra-company managerial processes in this paper we use the whole range of principles of budgeting from the point of view of practical implementation, and not from the point of view of the theoretical conceptual imperatives.